PEMBUATAN GAME 3D SURVIVAL HORROR “HOUSE OF MAZE” DENGAN FITUR VIRTUAL REALITY - Yudistira, Ferry Ruben; M, Viny Christanti; Haris, Darius Andana (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
“House of Maze” is a survival horror video game. The game is created with the purpose of providing a game that can create a sense of fear and shocking. Where the player also think looking for a way out the maze with various challenges, provide new experiences maze with three-dimensional view and the new feature virtual reality with Oculus Rift. Users positioned as a player who got stuck in a maze with a dog house and ghosts in it. Player must find a way out but can only walk and needed a candle as illumination. This Game created by game engine Unity with C# as programming language. Key words Survival Horror Game, Maze, Unity, C#, Virtual Reality, Game 3D, House of Maze